An Analysis of Action Competence Among Biology Education Students in the Context of Education for Sustainable Development - Sri Reski Ningsih; Dharma Ferry (Bioeduca : Journal of Biology Education, 2026)
Within the framework of developing Action Competence (AC) in Education for Sustainable Development (ESD), semester level is an important variable as it reflects students’ learning experiences, engagement, and academic maturity, as well as its contribution to conceptual understanding, willingness to act, and self-efficacy among prospective biology teachers. This study used a quantitative descriptive approach with a cross-sectional survey design involving 81 biology education students who were enrolled in or had completed the Environmental Knowledge course. Data were collected using the Likert-scale Action Competence in Sustainable Development (ACiSD) instrument and analyzed through normality testing, descriptive statistics, and one-way ANOVA using JASP. Results showed that students’ action competence toward ESD was in the high category (M = 74.87; SD = 9.42). All four indicators—conceptual understanding, willingness to act, self-efficacy, and outcome expectancy—also showed high scores across semesters. Although scores increased up to the sixth semester, ANOVA revealed no significant differences (p > 0.05), indicating that action competence development is more influenced by learning experiences than by semester level.